Acoustic horn tool assembly design for ultrasonic assisted turning and its effects on performance potential. Issue 3 (17th February 2022) - Arka, Girija Nandan; Sahoo, Susanta Kumar; Iqbal, Md Manzar; Singh, Subhash
ABSTRACT: Principally, hard material such as SS304 deployed a huge stress to process through conventional machining. Since, ultrasonic-assisted turning involves a synchronized ultrasonic vibration to the tool to establish intermittent cutting and could be a feasible choice. Thus, a comprehensive study was exercised to design horn-tool assembly for ultrasonic assisted turning and fabricated a potential experimental setup to address its machining potential to machine stainless steel. ANSYS® was incorporated to perform Harmonic and Modal analysis to obtained the horn-tool natural frequency, optimum shape and length respectively. The analysis showed 19925.5 Hz natural frequency and amplitude propagation approximately 4 times for 126 mm length along with 5 mm tool insert thickness. Further Taguchi method employed for the design of experiment and performed gray Taguchi for multi objective optimization. Investigation shows the induced cutting force and the surface roughness reduced significantly as low as to 53.89% and 54.5%, respectively, by ultrasonic turning. The machining parameters found optimum at a parametric setting: depth of cut 0.2 mm, feed 0.06 mm/rev and cutting velocity 38.48 m/min respectively favorable for getting low cutting force and high surface finish. Finally, results of the experiment invoked that ultrasonic assisted turning is a promising technique for hard material.